Measuring socio-economic indicators for climatic analysis - Ibrahim, Illyani (PMJ journal, 2017)
Socio-economic indicators are important indexes to measure the effect of human activities towards climate. This paper aims to study on the two main socioeconomic indicators for the urban area, namely population and GDP, to determine the relationship between these variables and climate condition. The State of Selangor, Malaysia was chosen as the study area as this state is among the highest GDP contributors to the country. Secondary data was used for this study by utilising datasets from Statistical Department and Department of Meteorology. The model derived shows that climate condition is moderately dependence of population and GDP. Further analysis can focus on more important socioeconomic variables which may contributed to the climate condition in the urban area.